METHOD FOR SYNTHESIS TEXTURE FILTERING THE IMAGE BACK-TRACING. DIMENSIONAL CASE - Gusiatin, V. M.; Chagovets, Ya. V.; Kozhushko, D. G. (Radio Electronics, Computer Science, Control, 2008)
A method of texture filtering for the synthesis of images by ray tracing method. The essence of the method is to implement filtering in the texture plane. Suggest approximation of the actual projection of the filter in the texture plane.